Utilization of Artificial Intelligence to Support the Development of Teaching and Project Modules - Djajasoepena, Rafie; Setiawan, Iwan; Bhakti, Muhammad Agni Catur; Purnomo, Ariana Tulus; Ayu, Media Anugerah; Alibasa, Muhammad Johan; Wandy, Wandy (Center for Research and Community Service of Sampoerna University, 2024)
Artificial Intelligence (AI) is now commonly used in many sectors, including education. Utilizing AI technology to support learning does not mean replacing the role of educators. The critical role of educators is to teach, educate, and train students to build their skills, knowledge, and morals, which are irreplaceable by AI. SMP Negeri 174 Jakarta is a public junior high school in East Jakarta and would like to receive guidance to upgrade teachers’ competencies in AI. The event lasted half a day and about 39 teachers participated in this agenda. The overall community service activities began in early April 2024 and ended on May 15, 2024, and all main activities were completed 100%. The session was successfully delivered in around two hours with days of preparations. Future recommendation is to include similar topics related to academic activities and technology.